Euro-Mediterranean relations after the Arab Spring persistence in times of change - Horst, Jakob; Jünemann, Annette 1959-; Rothe, Delf (Routledge, 2016)
The 'Arab Spring' triggered paradigmatic shifts but, despite these changes, much in the Euro-Mediterranean region remains the same. Utilising 'Logics of Action', an innovative theoretical framework designed to capture the complexity of political interaction in one of the fastest changing regions in the world, this book discusses developments in the region before and after the Arab Spring that can be characterised by a continuation of the norm. Expert contributors identify patterns of interaction between governmental institutions, economic entrepreneurs, religious groups and other diverse actors that withstood these historical changes and explore why these relationships have proved so robust. Connecting a unique sample of case studies on changing and persistent 'Logics of Action' within the Euro-Mediterranean space this book provides a pivotal contribution to our understanding of political interaction between North Africa, the Middle East and the European Union. Offering a completely new perspective on the events of the 'Arab Spring' it identifies something that seems paradoxical at first sight; persistence in times of radical change.